Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Review: 71



Work Step by Step

$\dfrac{4}{a-1}+2=\dfrac{3}{a-1}$ Multiply the whole equation by $a-1$: $(a-1)\Big(\dfrac{4}{a-1}+2=\dfrac{3}{a-1}\Big)$ $4+2(a-1)=3$ Solve for $a$: $4+2a-2=3$ $2a+2=3$ $2a=3-2$ $2a=1$ $a=\dfrac{1}{2}$ Since the initial equation is not undefined for this value of $a$, we have found the answer. The solution to this equation is $a=\dfrac{1}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.